Identifying exceptional cultural profiles in the world using Foursquare data - Coelho, Paulo Henrique de S; Melo, Pedro O. S. Vaz de; Alvim, Mario S (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
people around the world to daily record and share they activities, tastes and habits making them accesible both by other users and potential researchers. Analyzing the activity of the members in those networks, it’s possible to identify shared behavior patterns that determine the formation of virtual groups of people who are culturally close even not knowing each other, and whose boundaries cross over the political and natural borders of countries in the real world. In this paper, we propose the development of a information model capable of explain how those virtual groups are formed and what is it’s connexion with typical cultural habits that define certain countries and societies.